Implikasi Divergensi Usia Pengajar terhadap Tingkat Penyelesaian pendidikan di Sulawesi Selatan, Utara, Tenggara, Selatan tahun 2023 - Andi Aisyah Humairah; Irwandha Dwi Iestya; Wina Sunarti (CV. Multi Kreasi Media, 2024)
This research and journal aims to analyze the implications of teacher age divergence on education completion rates in South, North, Central, and Southeast Sulawesi Provinces using education completion data from 2023. We employed quantitative research methods to collect and analyze data from various sources. The results show that teacher age does not have a significant influence on education completion rates in South, North, Central, and Southeast Sulawesi Provinces.